공기업의 임원교체와 중도퇴임이 경영성과에 미치는 영향 - 유승원 (12608, 2012)
This study examines whether the executive turnover and the executive resignation during the term of office affect the performance of Korean state-owned enterprises. The executive turnover in the paper means the comprehensive change of the executives which